PROCESSING OF GYPSUM-BEARING MATERIALS IN THE BRONZE AGE GONUR DEPE ARCHEOLOGICAL SITE (SOUTHEAST KARAKUM DESERT) - L.Ya. Kabanova; A.M. Yuminov; I.A. Blinov (Минералогия)
The technology of preparation of an ancient binder mixture used in construction work at the Gonur Depe archeological site (Southeast Karakum desert) is interpreted on the basis of study of its mineral composition and textural-structural features. The material is composed of thin prismatic-angular and fibrous aggregates of reduced gypsum (60–70 %) and β-bassanite (3 %) enclosed in clay-siliceous matrix (20–30 %). The mixture also contains grains of quartz (5–10 %), feldspar (up to 1%), mica (up to 1 %) and other minerals. The mixture was produced from a crushed natural gypsum stone, which was calcinated in air. In this case, gypsum is converted to β-bassanite and partly to anhydride. The morphology and sizes of mineral particle confirm the presence of the calcination stage up to 200 °C. The further addition of water to a dry mixture caused rapid thickening and cementation of the material, which could be used for whitewashing and plastering of the walls.